SOCIAL INEQUALITY IN TEACHERS REVIEWED BASED ON DIFFERENCES IN TEACHER EMPLOYMENT STATUS IN DKI JAKARTA - Irzandy Maulana (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2021)
This study discusses the social gaps in teachers reviewed from differences in teacher staffing status in DKI Jakarta. The status of existing teachers is; Civil Servant Teachers (PNS), Individual Employment Contract Teachers (KKI), and School Honorer Teachers. The research aims to see how gaps occur in teachers with different staffing statuses. The study used the concept of material disparity and Dahrendorf's authority to look at gaps in teachers. Previous studies of teacher inequality have been limited to policy gaps in teachers and teacher welfare gaps. This study shows that differences in teacher staffing status can lead to material and authority gaps occurring in teachers. This study uses qualitative case studies with informants of civil servant teachers, KKI teachers, and school honorer teachers in DKI Jakarta as research subjects.